Strength and power qualities are highly associated with punching impact in elite amateur boxers - Loturco, I.; Nakamura, F. Y.; Artioli, G. G.; Kobal, R.; Kitamura, K.; Cal Abad, C. C.; Cruz, I. F.; Romano, F.; Pereira, L. A.; Franchini, E. (The Journal of Strength and Conditioning Research, 2016)
This study investigated the relationship between punching impact and selected strength and power variables in 15 amateur boxers from the Brazilian National Team (9 men and 6 women). Punching impact was assessed in the following conditions: 3 jabs starting from the standardized position, 3 crosses starting from the standardized position, 3 jabs starting from a self-selected position, and 3 crosses starting from a self-selected position. For punching tests, a force platform (1.02 × 0.76 m) covered by a body shield was mounted on the wall at a height of 1 m, perpendicular to the floor. The selected strength and power variables were vertical jump height (in squat jump and countermovement jump), mean propulsive power in the jump squat, bench press (BP), and bench throw, maximum isometric force in squat and BP, and rate of force development in the squat and BP. Sex and position main effects were observed, with higher impact for males compared with females (p = 0.05) and the self-selected distance resulting in higher impact in the jab technique compared with the fixed distance (p = 0.05). Finally, the correlations between strength/power variables and punching impact indices ranged between 0.67 and 0.85. Because of the strong associations between punching impact and strength/power variables (e.g., lower limb muscle power), this study provides important information for coaches to specifically design better training strategies to improve punching impact.